Promoting Responsible Ecotourism through Environmental Initiatives at Coban Glotak, Malang Regency, East Java, Indonesia - M Febri Pujiansyah; Mochammad Nugroho Nastangin; Muhammad Qamar Arshad; Moch Gybrant Putra Wibowo; Mochammad Riski Saputra; Putra, Rivandi Pranandita; Mochammad Tri Herwanto; Vita Ayu Kusuma Dewi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Coban Glotak tourism area, located in Malang Regency, East Java, represents a natural attraction with substantial ecological and aesthetic value. Nevertheless, it continues to encounter significant challenges in terms of management. Inadequate accessibility, the lack of proper directional signage, and an ineffective waste management system constitute the principal obstacles to its development as a sustainable tourism destination. This initiative was undertaken as a contribution towards the achievement of the Sustainable Development Goals (SDGs), particularly SDG 3 (good health and well-being), SDG 11 (sustainable cities and communities), and SDG 15 (life on land). The approach adopted included environmental observation to identify prevailing issues, interviews with local site managers, and the implementation of field-based actions. The interventions comprised litter removal along the tourist pathways, installation of directional and safety signage, placement of safety ropes on steep or hazardous trails, and trimming of overgrown vegetation that impeded access. The outcomes indicated marked improvements in cleanliness, visitor comfort, and overall safety, in addition to fostering a collective sense of environmental awareness. These findings demonstrate that modest yet well-structured interventions, grounded in local community involvement, can yield positive impacts on the sustainable management of tourism sites. Furthermore, such practices may serve as replicable models for the development and conservation of other natural tourism destinations.